2020
DOI: 10.1016/j.jcv.2020.104592
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a qualitative rapid chromatographic immunoassay to diagnose COVID-19 in patients in a middle-income country

Abstract: Highlights COVID-19 diagnosis; high sensitivity and specificity qualitative rapid chromatographic immunoassays; can be used for the diagnosis of RT-PCR-negative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…The color change was compared to the assay standard. 23 For viral culture, Vero cells (ATCC CCL-81) were used as previously described. [24][25][26] Vero CCL81 cells were cultured in Dulbecco minimal essential medium supplemented with heat-inactivated fetal bovine serum (10%) and antibiotics/antimycotics (Cultilab).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The color change was compared to the assay standard. 23 For viral culture, Vero cells (ATCC CCL-81) were used as previously described. [24][25][26] Vero CCL81 cells were cultured in Dulbecco minimal essential medium supplemented with heat-inactivated fetal bovine serum (10%) and antibiotics/antimycotics (Cultilab).…”
Section: Methodsmentioning
confidence: 99%
“…The result was read in 15 min by three people that had received appropriate training. The color change was compared to the assay standard 23 …”
Section: Methodsmentioning
confidence: 99%
“…The use of POC-based tests for rapid antibody detection can be helpful in identifying patients at different stages of infection, due to the early production of IgM followed by IgG response, although, in patients with COVID-19, the response of IgM and IgG could be simultaneous [ 7 , 8 ]. Our results demonstrated that overall sensitivity achieved by Bioclin LFIA (85.71%) with whole blood samples is compared to those obtained with serum or plasma for Wondfo (from 71.7 to 85.8%) [ 12 14 ] and Livzon (86.7%) [ 15 ], in contrast to Livzon and Wondfo LFIAs which showed sensitivities below 50%.…”
Section: Discussionmentioning
confidence: 62%
“…A better sensitivity for capillary whole blood with Wondfo LFIA test was reported by Silveira et al [ 13 ] at 77.1% in 83 volunteers with positive RT-PCR results at least 10 days before the LFIA test. In a larger study with hospitalized patients, Costa et al [ 12 ] evaluated the Wondfo LFIA, in serum samples or plasma, and obtained a sensitivity of 85.8%. In another evaluation of the Wondfo LFIA, Wu et al [ 17 ] have shown a sensibility of 75.8% in serum samples.…”
Section: Discussionmentioning
confidence: 99%
“…The use of POC based tests for rapid antibody detection can be helpful in identifying patients at different stages of infection, due to the early production of IgM followed by IgG response, although, in patients with COVID-19, the response of IgM and IgG could be simultaneous. Our results demonstrated that overall sensitivity achieved by Bioclin LFIA (85.71%) with whole blood samples is compared to those obtained with serum or plasma, in contrast to Livzon and Wondfo LFIAs which showed sensitivities below 50% [7-10].…”
Section: Discussionmentioning
confidence: 68%